2010
DOI: 10.1007/s00340-010-4177-5
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond coherent pulses in the keV range from inner-shell transitions pumped by a betatron source

Abstract: International audienceWe present a new method to generate ultra-short X-ray laser pulses by using the recently demonstrated laser-driven betatron source to photo-pump inner-shell transitions. The proposed compact set-up will then open the route to a wide range of applications. The betatron spectrum and ion-population kinetics are modeled and the temporal evolution of the gain coefficient for the K-α transitions is assessed. Using measured values of divergence, duration, and number of photons per pulse of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The photoionization inner-shell x-ray laser scheme was originally proposed by Duguay and Rentzepis [3], and since then, several possible targets and pumping schemes were studied in theory [9][10][11][12][13][14][15][16]. Although experimental attempts have been made and an inner-shell laser was demonstrated in the blue spectral domain [17] in 1983 and in the EUV region by Auger-decay pumping [18], the development of powerful XFELs [19][20][21][22][23] was needed to demonstrate this scheme in the soft x-ray spectral region at 1.45-nm wavelength by a laboratory-based experiment [1].…”
Section: Introductionmentioning
confidence: 99%
“…The photoionization inner-shell x-ray laser scheme was originally proposed by Duguay and Rentzepis [3], and since then, several possible targets and pumping schemes were studied in theory [9][10][11][12][13][14][15][16]. Although experimental attempts have been made and an inner-shell laser was demonstrated in the blue spectral domain [17] in 1983 and in the EUV region by Auger-decay pumping [18], the development of powerful XFELs [19][20][21][22][23] was needed to demonstrate this scheme in the soft x-ray spectral region at 1.45-nm wavelength by a laboratory-based experiment [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work [14], we have shown that the nitrogen density has a strong influence on the local gain value. More precisely, the peak gain value scales linearly with the gas density for pulse durations shorter than 20 fs.…”
Section: Influence Of the Driving Laser Powermentioning
confidence: 98%
“…Details of the atomic models for nitrogen and neon are given elsewhere [14]. Therefore only a brief description is given here.…”
Section: Radiative Transfer Calculations In Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…∼ 6 m at the speed of light) [3] which prevents from demonstrating the lasing scheme. In order to overcome these problems, the possibility of using betatron radiation, as produced by a laser-driven relativistic electron beam, and longitudinal pumping have been recently proposed (figure 3) [4,5]. …”
Section: Introductionmentioning
confidence: 99%